STUDI PENATAAN KAWASAN PARIWISATA MANGROVE DI KABUPATEN TANGERANG (OBJEK STUDI: URBAN AKUAKULTUR KETAPANG) - Calvin Jonathan; Priyendiswara Agustina Bella; Liong Ju Tjung; I G. Oka Sindhu Pribadi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Tourism development in an area has great potential or benefits for a region. The Ketapang Urban Aquaculture area is no exception in the Tangerang district, precisely in the Mauk District on Jl. Raya Tanjung Kait, Ketapang village. It is a tourist area of a mangrove conservation park and in it there is fish and shrimp cultivation. The development of the Ketapang Urban Aquaculture program focuses on mangrove forest conservation, but also organizes the area around the coastal area and builds several supporting infrastructures, and seeks to increase the economy of the people in the village so that it can become a new tourist area/destination in the coastal areas of the Tangerang district. This area has also been equipped with various supporting facilities to support tourism activities in the area, such as spots for taking pictures with mangrove views in the background, parking lots, jogging tracks, lighting for the night and others, but the facilities are still lacking to become a good tourism area. , such as the absence of a place to eat, the absence of a pavilion/gazebo for visitors to rest. Therefore the author wants to look for potentials and deficiencies so as to be able to provide an appropriate arrangement plan for the Ketapang urban aquaculture area. Where this arrangement is carried out using several analytical methods, such as location analysis, site analysis, attractiveness analysis, best practices analysis, and several other analyses. And some of this analysis is useful for looking for weaknesses and strengths that can support the arrangement of the urban aquaculture Ketapang area so that it becomes an even better tourism area and becomes superior tourism in the Mauk area. Keywords: urban aquaculture; mangroves; arrangement of tourism areas Abstrak Pengembangan pariwisata pada suatu kawasan memiliki potensi atau manfaat yang besar bagi sebuah wilyah. Tidak terkecuali pada kawasan Ketapang Urban Akuakultur berada di kabupaten Tangerang tepatnya di Kecamatan  Mauk di Jl. Raya Tanjung Kait, desa Ketapang. Merupakan sebuah Kawasan wisata taman konservasi mangrove serta didalamnya terdapat budidaya ikan dan udang. Pengembangan program Ketapang Urban Aquakultur berfokus pada konservasi hutan mangrove, namun juga melakukan penataan pada wilayah sekitar daerah pesisir serta membangun beberapa infrastruktur pendukung,dan berupaya menaikan ekonomi masyarakat didesa tersebut sehingga bisa menjadi kawasan/destinasi wisata baru di daerah pesisir laut kabupaten Tangerang. Kawasan ini juga sudah dilegkapi berbagai fasilitas pendukung guna Mendukung kegiatan pariwisata di Kawasan tersebut, seperti spot untuk berfoto dengan latar belakang pemandangan mangrove,tempat parkir,jogging track,lampu penerangan untuk malam hari dan lainnya namun fasilitasnya dirasa masih kurang untuk menjadi Kawasan pariwisata yang baik, seperti tidak adanya tempat makan, tidak adanya pendopo/gazebo untuk pengunjung beristirahat. Maka dari itu penulis ingin mencari potensi serta kekurangan sehingga mampu memberikan rencana penataan kepada Kawasan Ketapang urban akuakultur yang sesuai. Yang mana penataan ini dilakukan dengan beberapa metode analisis, seperti analisis lokasi, analis tapak, analisis daya tarik, analisis best practices, dan beberapa analisis lainnya. Dan beberapa analisis ini berguna untuk mencari kekurangan serta kelebihan yang bisa mendukung penataan Kawasan Ketapang urban akuakultur agar menjadi Kawasan pariwisata yang lebih baik lagi dan menjadi pariwisata unggul didaerah Mauk.